Curcumin prevents muscle damage by regulating NF-kB and Nrf2 pathways and improves performance: an in vivo model - Şahin, Kazım; Pala, Ragıp; Tuzcu, Mehmet; Özdemir, Oğuzhan; Orhan, Cemal; Şahin, Nurhan; Juturu, Vijaya (My University, 2016)
Purpose Exercise (Ex) increases reactive oxygen species and impairs antioxidant defense systems. Recent data suggest that curcumin (CW) possesses peroxisome proliferator-activated receptor gamma activity and anti-inflammatory properties. Therefore, this study was designed to investigate the effects of CW supplementation on Ex performance, endurance, and changes in serum and muscle proteins in rats after exhaustive Ex. Materials and methods Twenty-eight (28) male Wistar rats (age: 8 weeks and body weight: 180±20 g) were divided into four treatment groups: 1) control (C; no Ex), 2) C + CW (no Ex + CW), 3) C + Ex, and 4) C + Ex + CW (Ex + CW). CW was administered as 100 mg/kg CurcuWin®, providing 20 mg of curcuminoids daily for 6 weeks. A motor-driven rodent treadmill was used to carry out the Ex protocols. During a 5-day period, animals in chronic Ex groups were put through different regimens: day 1, 10 m/min for 10 minutes; day 2, 20 m/min for 10 minutes; day 3, 25 m/min for 10 minutes; day 4, 25 m/min for 20 minutes; and day 5, 25 m/min for 30 minutes. Animals were exercised at 25 m/min for 45 min/d for 5 d/wk for 6 weeks. Blood and muscle samples were analyzed for muscle markers, oxidative stress, and antioxidant markers. Results Lactate and muscle malondialdehyde levels decreased in the CW-treated groups (P<0.0001). However, activities of antioxidant enzyme levels increased in the CW-treated groups. Run to exhaustion (minutes) improved in the CW-treated groups. Muscle nuclear factor-?B (P<0.05) and heat shock protein 70 (P<0.05) levels were much lowered in the CW treated group followed by Ex group. In addition, muscle inhibitors of kappa B, peroxisome proliferator-activated receptor gamma coactivator 1-alpha, thioredoxin-1, sirtuin 1, nuclear factor (erythroid-derived 2)-like 2, and glucose transporter 4 protein levels in the Ex + CW group were higher than those in the control and Ex groups (P<0.05). Conclusion This study suggests that novel CW has the potential to help prevent muscle damage by regulating the nuclear factor-?B and nuclear factor (erythroid-derived 2)-like 2 pathways and improve the performance and nutritional values of CW.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Exercise; Curcumin; Oxidative stress; NF-kB; Nrf2; Muscle